Big Nate flips out - Peirce, Lincoln (New York, NY; HarperCollins, 2013)
"In this latest misadventure, Nate, the all-time record- holder for detentions, gets to see how the other half lives as he follows his best friend Francis's example and becomes a total neat freak; has Nate totally flipped out?" --Provided by publisher.
Keywords: Behavior -- Fiction; Orderliness -- Fiction; Friendship -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Humorous stories